2020
DOI: 10.7196/samj.2020.v110i10.14693
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical audit to evaluate postoperative quality of recovery in adults at New Somerset Hospital, Cape Town, South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The 25.1% worsening in the day 1 severe pain score is greater than in 3 other studies where a decline in the severe pain score was 6.2%, 35 12%, 26 and 15%, 36 respectively. In a South Africa context, Sikhakhane et al 21 found that 12% of patients complained specifically about postoperative pain in an open-comments section, while Ally et al 22 noted that postoperative pain negatively contributed toward their patient population’s QoR. From this, it can be surmised that postoperative pain is a major contributor toward poor QoR within a South African context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 25.1% worsening in the day 1 severe pain score is greater than in 3 other studies where a decline in the severe pain score was 6.2%, 35 12%, 26 and 15%, 36 respectively. In a South Africa context, Sikhakhane et al 21 found that 12% of patients complained specifically about postoperative pain in an open-comments section, while Ally et al 22 noted that postoperative pain negatively contributed toward their patient population’s QoR. From this, it can be surmised that postoperative pain is a major contributor toward poor QoR within a South African context.…”
Section: Discussionmentioning
confidence: 99%
“…15 This is important in a resource-constrained South African setting, where studies on QoR are limited. 21,22…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…48 Currently, instruments used to gauge pain severity include the Visual Analog Scale (VAS), the Numerical Rating Scale (NRS), the McGill Pain Questionnaire (MPQ) and the Brief Pain Inventory (BPI). 36,49 The VAS and NRS are unidimensional and only assess pain intensity. The two tools use a score based on the patient's self-reports of the presence and severity of their pain.…”
Section: Cause Analysis Inadequate Postoperative Pain Assessmentmentioning
confidence: 99%